Co-aggregation: Interaction of Candida albicans, Actinomyces naeslundii and Streptococcus mutans - Arzmi, Mohd Hafiz; Dashper, Stuart; Reynolds, Eric; McCullough, Michael (2014)
Introduction: Microbial interactions have been found to be associated with the development of oral biofilms. Inter-kingdom co-aggregation within biofilms may be important in enhancing adherence, altering epithelial cytokines, which may ultimately be involved in carcinogenesis. Objective: Our aim was to determine co-aggregation of C. albicans (CA), A. naeslundii (AN), and S. mutans (SM). Methods: Four C. albicans ATCC strains (32354, MYA-2876, 90234, and 18804), two HIV isolates (genotype-A and genotype-B), 2 oral cancer isolates (OC1 and OC2), A. naeslundii (NCTC 10301) and S. mutans (Ingbritt) were used in this study. In-auto- aggregation assay, C. albicans was grown in RPMI-1640 and artificial saliva medium (ASM) to produce hyphae and yeast forms respectively, whereas bacteria were grown in BHI. C.albicans, A. naeslundii and S. mutans were standardised to give 106 cells/mL, 107 cells/mL and 108 cells/mL respectively, in co-aggregation buffer followed by a 1h incubation at 25°C. The absorbance difference (ΔAbs) between 0h and 1h was recorded. To study co-aggregation, the same protocol was repeated, except combinations of microorganisms were inoculated in the same vial. Results: The mean ΔAbs percentage of C. albicans was significantly higher in ASM than RPMI-1640. The mean ΔAbs percentage of CA-AN, CA-SM and CA-AN-SM was 25.6%, 23.2% and 42.1% lower than C. albicans alone, respectively, in RPMI-1640, whereas in ASM, only CA-AN had a lower ΔAbs percentage by 15.3%. CA-SM and CA-AN-SM in ASM increased ΔAbs percentage by 6.5% and 23.6%, respectively. Conclusion: This study demonstrates that inter-kingdom aggregation of C. albicans, A. naeslundii and S. mutans is dependent on the morphological form of C. albicans. Co-aggregation occurs much more in the yeast than the hyphal form, which may have a relevance to the development of oral biofilms and ultimately oral carcinogenesis.